“Islamic Moderation” in Perspectives: A Comparison Between Oriental and Occidental Scholarships - Tazul Islam; Amina Khatun (UIN Sunan Gunung Djati Bandung, 2015)
‘Islamic moderation’ has received a great deal of academic and media attention both in the West and in the East. Yet, the denotation of the very term still remains abundantly paradoxical as different regions and contexts provide different sheds of meanings. In the western scholarship, Islamic moderation is concerned with liberal social norms, hermeneutics, political pluralism, democratic process, organizational affinities, and views of state legitimacy over the monopoly of violence, some kind of adaptation, willingness to cooperate or compromise. However, it is by no means exhaustive as its definition in Islamic scholarship provides some unlike constituents. To define moderation, Muslim scholars, firstly explores to lexical meanings of its Arabic substitute “wasatiyyah”. Secondly, they explore the textual meanings of the word “wasatiyyah” used in the orthodox text i.e the Quran and traditions (Sunnah) of the Prophet Muhammad (pbuh). According to them, moderation is a best suited, justly balanced or middle position between two extremes i.e. extremism and laxity. Their use of the term, is contextualized in terms of counter-extremism, modest socio-religious behaviour and temperate legal position. This research finds out a considerable textual and contextual difference in the use of the term ‘Islamic moderation’ between the East and the West. Hence, this study aims to explore the lack of integration between both scholarships in this issue.